The Effect of Quantum Model Learning through The Ability to Finish Mathematics Report Text Question in Elementary School - Prawiyogi, Anggy Giri; Suhardiman, Sani; Supriadi, Hery (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is aimed to find out the effect of quantum learning model through the ability to finish report text at the 4th grade students’ on mathematic subject at SDN Cengkong III Karawang. This research used quantitative method. Population used in this paper is all students in SDN Cengkong III there are 204 students. The sample is the students at 4th B as the experiment class and 4th A as controlled class. the writer uses the essay question as The data collection technique to finish report text of mathematic question. This paper compared the use of quantum learning model in finishing mathematic report text and those who are not. Data analysis technique to test and hypothesis conducted with statistic t-test paired sample test, n= 20 which means shows hypothesis is accepted . based on the research the writer can summarize that quantum learning model in teaching and learning process and in finishing mathematic report text question at 4th grade students in SDN Cengkong has a strong relationship